Criminalization of Teachers Due to Case of Bullying Committed by Students - Joshua Irawan; Jamin Ginting; Teguh Prasetyo; Fajar Sugianto; Andrew Johnathan Setia (IJCLS (Indonesian Journal of Criminal Law Studies), 2025)
Children are individuals who are not yet adults and have a fundamental right to education. A child's education starts at the family level and continues at an educational institution like a school. Teachers play a crucial role in education and are responsible for instructing their students. In addition to this responsibility, teachers must uphold laws, regulations, and ethical codes as specified in Article 20 of Law No. 14/2005. This includes adhering to child protection laws outlined in Law No. 35/2014. Everyone needs to protect children from violence, as Article 76C of Law No. 35/2014 explicitly prohibits any person from committing or allowing violence against children. The law also mandates teachers to protect their students from violence, as stated in Article 9(1a) and Articles 54(1) and (2) of Law No. 35/2014. Issues arise when teachers allow bullying to occur among their students. This neglect constitutes a violation of Article 76C of Law No. 35/2014. This study uses a normative legal methodology to apply child protection rules to teachers who ignore bullying among their students. The study concludes that teachers who tolerate bullying violate Article 76C of Law No. 35/2014, as this neglect causes suffering to children. Such teachers could face criminal sanctions as outlined in Article 80 of Law No. 35/2014. The research team suggests increased criminal penalties for teachers who allow such neglect should be imposed.